Changing the World: Changing the World: Global Perspectives on Social Movements/Activism - Enos, Sandra (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
It is well recognized that we live in a time of unprecedented change. Rapid social, political and economic transformations are the hallmarks of our postindustrial, post-modern society. These transformations are in part the result of work done by activists to change the world. For example, consider how the anti-apartheid movement in South Africa, the Solidarity Movement in Poland, and the women’s movement in the United States have created conditions for significant political changes. In other instances, activists have responded to large-scale changes, like the globalization of the economy, the impacts of development on populations and the environment, and have organized efforts to resist changes, and to develop critiques of the impacts of these changes. For example, environmental degradation and loss of habitat, child labor in less developed nations, and other developments have sparked social movements directed at mitigating and resisting the effects of large scale changes.